Methicillin-resistant Staphylococcus aureus (MRSA) bacteremia: Correlations between clinical, phenotypic, genotypic characteristics and mortality in a tertiary teaching hospital in Malaysia - Sit, Pik San; Teh, Cindy Shuan Ju; Idris, Nuryana; Ponnampalavanar, Sasheela (Elsevier, 2018)
Methicillin-resistant Staphylococcus aureus (MRSA) bacteremia is a serious infection that can result in significant morbidity and mortality. A retrospective cohort study was conducted to determine the predictors of mortality in patient with MRSA bacteremia correlating with clinical, phenotypic and genotypic characteristics of the relevant strains. Most of the bacteremia cases were healthcare-associated (P < 0.0001). Older age (P < 0.0001) and comorbidities (diabetes mellitus, hypertension and chronic kidney disease) were identified as the risk factors for MRSA bacteremia. All the strains were sensitive to vancomycin. Most MRSA strains causing bacteremia belonged to SCCmec type III-ST239 and exhibited pulsotype H. According to the multivariate analysis, age ≥ 60 years old (P = 0.022), female gender (P = 0.0003), pneumonia (P = 0.011) as source of infection as well as high APACHE II, Charlson comorbidity Index and Pitt's bacteremia scores were significantly associated with patient's mortality. There were emergence of MRSA clones such as SCCmec type I-ST152, SCCmec type V-ST45 and SCCmec type V-ST951 that was discovered for the first time in Malaysia. To our knowledge, this is the first study correlating the clinical, phenotypic and genotypic characteristics of patients with MRSA bacteremia as well as determining the risk factors for mortality in Malaysian hospital.